(untitled) (Bioagro, 2026)
Potato is a fundamental crop for global food security; however, root-knot nematodes threaten its production. The aim of this study was to identify Meloidogyne species and assess the response of different potato varieties to this pathogen. Nematode populations were analyzed through biochemical characterization using esterase isoenzymes, identifying four species: M. incognita (Esterase I1, I2), M. arenaria (Est. A1, A2), M. hapla (Est. H1, H2), and M. ethiopica (Est. E3). Subsequently, thirteen potato cultivars were evaluated under greenhouse conditions, in pots, and inoculated with 5,000 eggs and J2 juveniles of nematodes. After 55 days, the number of galls, eggs, and the reproduction factor (RF) were measured. The Yungay cultivar exhibited the highest susceptibility, as evidenced by the high number of galls (25.68), eggs (74,633.3), and a high reproduction factor (RF) of 19.24. In contrast, the Ccompis, Venturana, and Ruki cultivars showed lower susceptibility, with the following results: galls (3.51, 3.56, and 1), eggs (1,783.3, 4,083.3, and 0), and RF (0.36, 0.472, and 0), respectively. Additionally, resistance was evaluated using three key indices: galls index (GI%), reproduction index (RI %), and RF. In this regard, the Yungay variety showed high susceptibility (IN=100%, IR=100%, RF=13.46), in contrast to resistant cultivars like Ruki (GI=5.5 %, RI=0 %, RF=0.00) and Andina (GI=15.3 %, RI=2.6 %, RF=0.35), which inhibited nematode penetration (GI%) and reproduction (RI %). This study provides key information on the resistance and susceptibility of potato cultivars to nematodes, which is useful for guiding management strategies and selecting appropriate varieties in areas with a high presence of root-knot nematodes.